What School Teachers Expect from Conversational Pedagogic Agents? - Silvia TAMAYO; Diana PÉREZ-MARIN (Ediciones Universidad de Salamanca, 2017)
Conversational Pedagogical Agents are interactive systems that teach students by assuming the role of teacher, student or companion through a natural language dialogue. If has been investigated a lot on the domains in which the agents can be used, the results in terms of educational effectiveness and level of satisfaction and motivation of the students. However, in the literature, there are not many examples of studies that reveal the opinion of school teachers on this type of educational technology. In this paper, we provide the results of a survey of 82 teachers to know what they expect from the agents. The following research questions will be answered: Q1) Do you know this educational technology? Q2) If so, are teachers used to integrate this type of technology in the classroom? and, P3) If teachers could design the agent, what characteristics do they consider to be the most appropriate? How should the agent react to different situations? From the results gathered, it is expected to provide information to all researchers, designers and teachers who want to integrate this type of educational technology in their classroom..